Implementasi Model Desain Bela H. Banathy dalam Meningkatkan Partisipasi Mahasiswa pada Mata Kuliah Akidah Akhlak - Rofiqoh, Nihayatur; Mukaffa, Zumrotul; Azizah, Khoridatul (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2025)
Teaching of Aqidah Akhlak tends to be theoretically oriented, lacking integration of the internalization of values and the actualization of morals into the realities of life. Bela H. Banathy’s design model presents an alternative systemic approach that emphasizes improving student learning performance by integrating all learning elements dynamically and comprehensively. Therefore, this study aims to examine the aspects of the Banathy design model applied in Aqidah Akhlak learning, as well as its supporting and inhibiting factors. This study uses a qualitative case study research method. Based on the analysis results, the Banathy design model has been implemented in the Aqidah Akhlak learning. Banathy’s systemic and holistic approach is evident in the lecturers’ efforts to prepare structured lesson plans (RPS), use participatory methods, and orient towards strengthening character. The successful implementation is due to innovative lecturers, active student participation, and the alignment of the institution’s vision that upholds Islamic values. The inhibiting factors include limited facilities, inadequate lecturer training, and the absence of institutional-level policies.